Selenium incorporation into calcite and its effect on crystal growth: An atomic force microscopy study - Renard, F.; Montes-Hernandez, G.; Ruiz-Agudo, E.; Putnis, Christine (2013)
The atomic processes leading to calcite growth are still debated. The presence of foreign impurities in solution is known to change the rate of step propagation during growth as well as the growth mechanism. Among trace elements, selenium, in the form of oxyanions, can incorporate into the calcite structure by replacing the carbonate group. In the present study, we record the effect of organic and inorganic selenium on calcite growth at room temperature by using in-situ time-lapse atomic force microscopy (AFM) and we confirm the observations by performing batch reactor experiments. Our results show that the incorporation of Se(IV) during calcite growth could be observed in-situ and the presence of this element modifies the morphology of growth features formed on a cleaved calcite surface, transforming typical pyramidal spiral growth hillocks into more complex heart-shape and tear-shape patterns. This effect is reversible as changing the solution back to a selenium-free composition recovers the original hillock pattern. Conversely, Se(VI) does not incorporate, but catalyzes the step propagation rate without changing the growth pattern. We have also observed that the presence of organic selenium (Se(-. II)), in the form of seleno-. l-cystine, has an effect on the nucleation of calcite crystals and their aggregation in clusters, but has no measurable effect on the morphology of growing steps at the calcite surface. These results indicate that calcite could represent a reservoir of selenite, whereas selenate would remain preferentially in solution, as observed in the composition of sea waters worldwide. © 2012 Elsevier B.V.